An Academic and Research-Based Study on the Background and Evolutionary Stages of the Mahdavi Movement: DOI: https://doi.org/10.5281/zenodo.17498410 (Khairulummah, 2024)
This research paper presents a historical and analytical study of the Mahdavi Movement in the Indian Subcontinent, tracing its origins, intellectual foundations, and stages of evolution. It establishes that Syed Muhammad Jaunpuri (RA) — later proclaimed by his followers as the “Promised Mahdi” — was in reality a devout, pious, and reformist scholar (‘Ālim-e-Bā‘amal) rather than a claimant of any new prophethood or independent religious authority.The study reveals that Syed Muhammad Jaunpuri’s true mission was centered on revival of Shari‘ah, purification of the self, and enjoining good and forbidding evil (Amr bil Ma‘rūf wa Nahy ‘an al-Munkar). He rose against the moral decay, religious formalism, and materialism prevalent among Muslims of his time, calling them back to the spirit of faith and sincere worship.However, after his death, some of his followers deviated from his original teachings and introduced exaggerated interpretations that had no direct connection with his authentic message. These later developments transformed a reformist and spiritual movement into an organized sectarian group known as the Mahdavi Movement. Their speculative interpretations of the Prophetic traditions on al-Mahdi distorted the essence of Jaunpuri’s original call.Drawing upon primary historical sources such as Muntakhab al-Tawarikh (Badayuni), Tabaqāt-e-Akbari (Nizam al-Din Ahmad), Akhbar al-Akhiyar (Abdul Haq Muhaddith Dehlavi), Nuzhat al-Khawatir, and Tadhkira by Abul Kalam Azad, the paper demonstrates that contemporary scholars — including Sheikh Ali Muttaqi, Sheikh Wajih al-Din Gujarati, Abdul Qadir Badayuni, and Abdul Haq Muhaddith Dehlavi — acknowledged Syed Muhammad Jaunpuri’s piety, knowledge, and sincerity, even if they disagreed with certain beliefs later attributed to his followers.The study concludes that Jaunpuri’s original message was one of spiritual renewal, adherence to Sunnah, and moral reformation, while the sectarian Mahdavi doctrines were later constructions. His so-called claim to Mahdiship was neither explicit nor doctrinal but the result of interpretive exaggerations by later adherents.